ETHICAL DYNAMICS IN THE IMPLEMENTATION OF REWARDS AND PUNISHMENT IN ISLAMIC EDUCATION - Andi Abd. Muis; Nur Amalina Abdul Rahman; Mardiah Wahyuni; Siti Rondhiyah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
Reward and punishment are pedagogical strategies commonly employed in  Islamic education to shape students’ behavior and moral character. However,  practices that are not grounded in ethical principles may lead to dependence on  external motivation and have negative effects on students’ psychological  development. This study aims to analyze the ethical dimensions of the  implementation of reward and punishment from the perspective of Islamic  education as well as contemporary critiques in studies of learning motivation. This  research adopts a qualitative approach through a literature review, with data  sources derived from the Qur’an, Hadith, books, and relevant scholarly journals.  The data were analyzed using a descriptive-analytical method, focusing on Islamic  ethical values such as justice (‘adl), compassion (rahmah), wisdom (hikmah), and  the educational orientation of tarbiyah. The findings indicate that reward is  effective in enhancing positive motivation when applied proportionally and  meaningfully, whereas punishment is justified only as an educational tool that aims  to educate without undermining students’ dignity. Contemporary psychological  critiques emphasize that an imbalance in the application of reward and punishment  may weaken intrinsic motivation. The implications of this study underscore the  importance of ethical and reflective instructional strategies that position reward  and punishment as supporting instruments for character education. Ethical  practices grounded in Islamic values contribute to the development of students’  intrinsic motivation and moral responsibility in accordance with the objectives of  Islamic education.